Benchmarking ports : An approach of a self-assessment tool for defining what to benchmark - Pérez Niño, Daniel Alejandro (2016)
Aiming to identify a suitable and updated benchmarking model, this paper initially entails an exhaustive literature review of benchmarking-related topics. After an evaluation of different benchmarking models found on the literature, a model entailing the best practices of the best in the literature, was identified and proposed as the path for this research.